Inhaled LAMA in the management of asthma: when to add an anticholinergic versus increase inhaled corticosteroid dose - Pawliczak, Rafał (Alergologia Polska - Polish Journal of Allergology, 2025)
Modern asthma treatment is standardised and based on scientific research data. Nevertheless, even established standards leave considerable room for interpretation and personalised patient management. This paper aims to demonstrate the significance and role of triple therapy (ICS/LABA/LAMA) in asthma, while assisting practising physicians in developing their own therapeutic approaches. The study reviews various aspects of LAMA use in asthma, including pathophysiology, clinical trials, and observational studies. The paper concludes with a proposal for therapeutic management based on current scientific evidence.